2003
DOI: 10.1088/0957-0233/14/10/308
|View full text |Cite
|
Sign up to set email alerts
|

Electrical techniques for monitoring the condition of lubrication oil

Abstract: The lubricating oil used in engines for vehicle and other applications is renewed according to a schedule specified by the manufacturer. This timetable is, naturally, very conservative, and makes no allowance for the way in which the engine is operated. Constant-speed operation (such as motorway use) is much less harmful to the lubricant than variable-speed operation, such as urban driving, during which the oil experiences extreme variations of temperature and engine speed. The net result of the conservative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 5 publications
1
18
0
2
Order By: Relevance
“…As the SPR curve for a used lubricant is shifted to the right up with respect to a fresh lubricant's SPR curve and the R min and u SPR values are increased (Figure 6(a)), this indicated that the dielectric permittivity 1 d of a used lubricant is higher than for a fresh lubricant. This result obtained through the analysis of lubricant optical properties is clearly concurred with a dielectric constantviscosity-mileage correlation measured by a capacitive sensor (Turner and Austin, 2003). In order to analyze statistically the difference between SPR measurements of fresh and used lubricants presented by informational parameters u SPR and R min , classic pattern recognition analysis (Tou and Gonzalez, 1974) was applied due to the following reasons.…”
Section: Spr-based Bayesian Classification and Monitoring Of Lubricansupporting
confidence: 70%
“…As the SPR curve for a used lubricant is shifted to the right up with respect to a fresh lubricant's SPR curve and the R min and u SPR values are increased (Figure 6(a)), this indicated that the dielectric permittivity 1 d of a used lubricant is higher than for a fresh lubricant. This result obtained through the analysis of lubricant optical properties is clearly concurred with a dielectric constantviscosity-mileage correlation measured by a capacitive sensor (Turner and Austin, 2003). In order to analyze statistically the difference between SPR measurements of fresh and used lubricants presented by informational parameters u SPR and R min , classic pattern recognition analysis (Tou and Gonzalez, 1974) was applied due to the following reasons.…”
Section: Spr-based Bayesian Classification and Monitoring Of Lubricansupporting
confidence: 70%
“…In automotive, lubricating oils are replaced according to a schedule specified by cars manufacturers: this strategy of maintenance is independent of the real state of oil, because does not take into account the operative conditions [7]. In fact, properties of lubricant depend on both external (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminants can alter the viscosity of oil, preventing proper lubrication. Soot, dirt, sludge, and oxidation products can make the oil too thick; conversely, dilution with unburned fuel may make the oil too thin (Turner and Austin, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Then it multiplies these by the oil capacity, as a greater oil capacity means the work is spread over a greater volume, and multiplies these by ten times the virgin oil's TBN (representing the oil's ability to handle the stress loads) to arrive at the oil change interval. Carey and Hayzen (2001) and Turner and Austin (2003) showed that the dielectric constant is another important indicator of oil quality that is easy to measure on-site. This test can reflect the presence of contaminants, such as water or particles, or changes in oil chemistry due to additive depletion or oxidation.…”
Section: Introductionmentioning
confidence: 99%